Seismic Design of a Four-Story Reinforced Concrete Pharmacy Building Using Special Moment Resisting Frames - M Basyar Syarif Hidayatulloh; Titin Sundari; Meriana Wahyu Nugroho; A’izzatul Khiyana (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2026)
The Pharmacy Building of Jombang Regional General Hospital is a four-story reinforced concrete building used primarily for pharmaceutical storage and office activities, requiring adequate structural strength and seismic resistance. This study aims to design the building’s upper structure using a Special Moment Resisting Frame (SMRF) based on SNI 1726:2019, SNI 1727:2020, and SNI 2847:2019. A quantitative structural design approach was employed, including preliminary member sizing, gravity and seismic load determination, three-dimensional modeling, response spectrum analysis, equivalent static force control, member capacity design, and seismic detailing. The results indicate that the building is classified as Seismic Design Category D on medium soil. The structural model achieves at least 90% modal mass participation. The design base shear is 2,834.37 kN in both principal directions after scaling. The floor slab is 120 mm thick with Ø12–200 reinforcement, while the main beam B1 is 500 × 700 mm with 6D22 longitudinal reinforcement at the support and 3D22 in the span. The main column K1 is 600 × 600 mm with 16D22 longitudinal reinforcement. Inter-story drift, column capacity, and the strong-column weak-beam requirement satisfy the adopted design criteria. The resulting design provides a practical basis for structural detailing and working drawings of earthquake-resistant pharmacy buildings.